Pediatric Otitis Media: Trends in Diagnosis and Treatment Protocols (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Otitis media (OM) is the most prevalent childhood disease, frequently leading to office visits, antibiotic prescriptions, and surgeries. By age 3, many children experience at least one acute episode of OM, particularly between 6 to 11 months. Recurrent acute otitis media negatively affects health-related quality of life (HR-QoL), necessitating timely diagnosis and treatment.Materials and Methods:This study examined the diagnosis and treatment practices of otitis media within a group of 100 patients, 0 to 18 years of age, from diverse healthcare settings in Iraq from February 2024 to February 2025. The cross-sectional research design facilitated the assessment of demographic, presenting complaints, treatment methods, and outcomes. The inclusion criteria entailed children who had clinically presented with a diagnosis of otitis media, while those with chronic ear issues or a history of surgery were excluded from the study. Data collection used standardized questionnaires, tympanometric pressure assessment, and the Pediatric Quality of Life Inventory (PedsQL) to assess the quality of life.The outcomes of the study group consisted of 60 male subjects (60%) and 40 female subjects (40%), with a mean age of 5.2 years. The common etiologies revealed included viral infections (45%) and bacterial infections (35%). The signs reported mainly involved ear pain (75%) and fever (50%). Management practices showed that 40% of the cases adopted a watchful waiting approach, whereas 35% were treated using antibiotics. The study results indicated a recurrence rate of 40%, while 45% of subjects experienced tympanostomy tube insertion. Additionally, quality of life scores improved from 60 ± 10 before treatment to 80 ± 8 after treatment (p < 0.05).Conclusion: The findings highlight the need for individualized methods in pediatric otitis management, specifically with preventive measures, strict treatment regimens, and close monitoring of recurrence patterns to improve the lives of children affected by the condition. Optimum prevention measures and treatment guidelines need to be investigated further to reduce the effects of otitis media on children.